What does it mean to think critically about (political) economy? An attempt to give an answer inspired by Max Horkheimer - Ronge, Bastian (Universidade Estadual Paulista / UNESP, 2018)
This paper addresses the question “What does it mean to think critically about (political) economy?” by reconstructing systematically the answer which Max Horkheimer gave when he became the director of the Institute for Social Research in 1931. On the basis of the criteria defined by Horkheimer in the 1930s for a critical theory of (political) economy, the article assesses the critical character of recent philosophical approaches towards the (political) economy: business ethics and philosophy of economics; Post-Marxism (Louis Althusser, Ernesto Laclau, Chantal Mouffe and J.K. Gibson-Graham); and the works of current representatives of the Frankfurt School (Axel Honneth and Rahel Jaeggi).